Perceiving learning regulation with Moodle: Implications for guidance - De Oliveira, P. D.; Da Veiga-Simão, A. M. V.; Costa Ferreira, P. A. N.; Ferreira, A. I. (Revista Española de Orientación y Psicopedagogía, 2022)
The present study aimed to understand how middle school students report how they self-regulate learning when using the Modular Object-Oriented Dynamic Learning Environment (Moodle) platform. To achieve this goal, a sample of middle school students (N=438) responded to the Self-Regulated Learning with Moodle Inventory (SRL-MI). Exploratory factor analysis (219 participants) and confirmatory factor analysis (219 participants) revealed good fit indices for the instrument used. In general, the results showed that students reflected on and reported how they self-regulated their learning when using the Moodle platform. Results also demonstrated how middle school students thought of themselves as learners. Through Item Response Theory, results showed that the students overestimated the way in which they self-regulated their learning in different phases (forethought: ? = 0.93, performance: ? = 0.88, and self-reflection: ? = 0.92). This reveals the difficulty students of this age group have and the inaccuracy with which they report how they self-regulate their learning when using the Moodle platform. Specifically, students revealed some difficulty in reporting strategic planning processes, the processes of regulating attention, and their self-reaction processes. Students demonstrated less difficulty in reporting self-efficacy beliefs about what they were able to learn, monitoring strategies and the reasons for success. Implications for guidance practice regarding the promotion of students’ self-reflection and suggestions for future research are discussed.